Performance of removing aqueous contaminant by zirconium based adsorbents: a critical review - Zhao, Dandan; Yang, Yi; Chen, J. Paul (Frontiers in Chemical Engineering, 2024)
The studies on materials for decontamination in aqueous solutions have increasingly received greater attentions. Such contaminants as heavy metals, arsenic, fluoride and phosphate are harmful to humans and aqueous species due to higher toxicity. Zirconium based adsorbents have become more attractive due to outstanding performance in decontamination. This article provides a comprehensive review of the performance and mechanisms of five types adsorbents: zirconium (hydro)oxides, zirconium hydrogen sulfate, zirconium based multiple metal typed adsorbents and zirconium impregnated complexes. Pseudo-first order, pseudo-second order and intraparticle diffusion equations are usually applied in describing the adsorption kinetics, while Langmuir and Freundlich isotherms are the most commonly used adsorption isotherms. The important mechanisms for update of contaminants are: ligand exchange between adsorbate and adsorbent, surface complexation with electron donation from adsorbate, and Lewis acid-base and electrostatic interactions. A series of successful studies demonstrate that the adsorbents are promising for removing aqueous contaminants.